2000
DOI: 10.1021/ja0004433
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of Alkenes by Amine Catalyst Precursors:  Implication of Aminium Ion and Radical Cation Intermediates

Abstract: We report herein the discovery of a novel process for epoxidation of alkenes, using Oxone, which, remarkably, is catalyzed by simple amines. This process, which does not rely on transition metal catalysts, utilizes Oxone/NaHCO 3 as the oxidant and simple, cheap, and readily available amines (see Table 1) as catalyst precursors for alkene epoxidation. The standard reaction procedure is illustrated in Scheme 1.Normally, Oxone buffered with NaHCO 3 in MeCN:H 2 O epoxidizes unfunctionalized alkenes only when oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 16 publications
3
37
1
7
Order By: Relevance
“…[72,73] Die Epoxidierung von 1-Phenylcyclohexen verläuft mit 46 % ee in Gegenwart von Schema 11. Ein fluorierter Organokatalysator zur stereoselektiven Epoxidierung von a,b-ungesättigten Aldehyden.…”
Section: Die Asymmetrische Epoxidierung Von Stilbenen Durch 2-(fluordunclassified
“…[72,73] Die Epoxidierung von 1-Phenylcyclohexen verläuft mit 46 % ee in Gegenwart von Schema 11. Ein fluorierter Organokatalysator zur stereoselektiven Epoxidierung von a,b-ungesättigten Aldehyden.…”
Section: Die Asymmetrische Epoxidierung Von Stilbenen Durch 2-(fluordunclassified
“…[3] In addition, chiral amines often possess pronounced biological activity in their own right and hence are in demand as intermediates for agrochemicals and pharmaceuticals. [4] Current methods for the preparation of enantiomerically pure chiral amines are largely based upon the resolution of racemates, either by recrystallization of diastereomeric salts [5] or by enzyme-catalyzed kinetic resolution of racemic substrates using lipases and acylases.…”
mentioning
confidence: 99%
“…68 These chiral oxaziridines were reported to oxidize non-functionalized sulfides (enantiomeric excesses up to 91% observed), 69 and to epoxidize olefins (up to 65% ee, 72 Aggarwal reported that a chiral derivative of pyrrolidine, (S)-2-(diphenylmethyl)pyrrolidine 84, allowed the conversion of 1-phenylcyclohexene into its corresponding epoxide in 57% ee (Scheme 21).…”
Section: Oxaziridine Mediated Epoxidationsmentioning
confidence: 99%